Judicial Review of Presidential Threshold Decisions: The Dynamics of Constitutional Injury - Achmad Zuhdi; Serhii Ablamskyi; Arya Anggara (Kosmik Hukum, 2025)
This study examines the Dynamics of Constitutional Injury Interpretation by the Constitutional Court in the Judicial Review of the Presidential Threshold Law, focusing on how the Court’s interpretation of constitutional harm has shifted in relation to granting legal standing to individual applicants. Historically, individual citizens have held the right to challenge laws they believe infringe on their constitutional rights. However, recent rulings show a shift where the Court restricts legal standing, allowing only political parties to challenge the Presidential Threshold Law. This restriction is based on two main reasons: changes in the electoral system, which now directly involves political parties, and the notion that voters’ increased knowledge diminishes the need for individual challenges. The study aims to critically assess whether these reasons hold sufficient weight to limit individual participation. Through a normative legal approach utilizing case and statutory analysis, findings reveal that limiting individual participation undermines democratic legitimacy, as the cited reasons lack substantive grounds to justify the restriction on individual legal standing in the constitutional review process.